Creating the Smallest BN Nanotube from Bilayer h‐BN. (28th October 2016) - Xu, Tao; Zhou, Yilong; Tan, Xiaodong; Yin, Kuibo; He, Longbing; Banhart, Florian; Sun, Litao
Abstract : Single‐wall nanotubes of boron nitride (BN) are among the most promising quasi‐1D materials with outstanding mechanical strength. However, synthesizing them in a controlled and reproducible way remains challenging. Here the authors show a technique of creating BN tubes by cutting bilayer BN sheets with an electron beam and interconnecting the two layers at an open edge. The in situ experiments in an electron microscope show that the spontaneous interlinking of the two layers leads to flattened tubular structures when a narrow ribbon is created. Below a certain width of the ribbon, van der Waals interaction between the layers is overbalanced by the stress in the layer so that the walls separate and a tube with circular diameter forms. The smallest stable BN tubes with a diameter of 0.45 nm, corresponding to a (3, 3) tube, can be produced by this technique. The diameter can only be decreased in discrete steps, showing that all possible BN tubes with a given axis alignment relative to the BN lattice can be made. This is a novel top‐down approach that allows the authors to create and study a variety of ultrathin nanotubes from related 2D materials. Abstract : Electron beam structuring provides a top‐down approach to create boron nitride (BN) tubes by cutting bilayer BN sheets. Covalent interlayer bonds form spontaneously at two parallel zigzag edges, resulting in formation of armchair BN tubes. The diameter can only be decreased in discrete steps to 0.45 nm, corresponding to a (3, 3) tube, which is the smallest tubes observed experimentally so far.